The effect of food safety education on handwashing practices in school canteens’ food handlers - Nik Rosmawati NH,; Wan Manan WM,; Noor Izani NJ,; Nik Nurain NH,; Razlina AR, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study aims to assess the effectiveness of a newly developed food safety education to improve the handwashing practices of food handlers in school canteens. A community-based intervention study was carried out over a 2-year period. Sixteen out of 98 primary schools were randomly selected and assigned into intervention and control groups using a simple random sampling method. The study population included food handlers who worked in the canteens of the school selected. The Food Safety Education Programme (FSEP) for the intervention group was developed based on the theory of planned behaviour. The main outcome measures used were handwashing practices from the observations carried out at baseline, 6-weeks (Post1) and 12-weeks (Post2) after the intervention. Out of 79 food handlers who participated in this study, 33 (41.8%) were in the intervention group and 46 (58.2%) were in the control group. Prior to FSEP, handwashing was not commonly practiced following critical events and the majority did not perform correctly. The time-effect of the mixed design analysis of variance showed a significant increase (p=0.004) in the mean percentage of the total observed handwashing practices from 29% at the baseline to 50.8% at Post1 (p=0.004). However, the intervention-effect of mixed design ANOVA did not show any significant difference in the handwashing practices (p=0.210). The FSEP was effective in improving the handwashing practices of the food handlers in the selected primary school canteens.